METAPHOR IN BARACK OBAMA’S SPEECHES - Nancy Kristiani Panggabean; Berlin Sibarani (State University of Medan, 2016)
This research deals with Metaphorical Patterns in Barack Obama’s speeches. Thisresearch uses a qualitative approach. The objective of the study were to find themetaphorical patterns in Barack Obama’s speeches. The data were collected fromthe speech of Barack Obama. The study revealed that there are five metaphoricalpatterns are used in Barack Obama’s speeches: general reifying, animizing andpersonifying metaphors, materializing abstract process, process, object orsubstance. The speech was the representative of his sayings to white people. Theresponses of white people were analyzed by theory and the responses are: whitepeople receive and felt happy because everything that he said about unity is goodin the speech.